Gig Economy: The Promise of Platform Work - Nursilah Ahmad; Zurina Kefeli@ Zulkefli; Noor Zahirah Mohd Si; Maya Puspa Rahman (Universiti Sains Islam Malaysia, 2024)
e-Proceedings of The 9th Islamic Banking, Accounting and Finance International Conference 2020 (iBAF2020) “Navigating the New Normal in Islamic Finance and Wealth Management” 10th – 11th November 2020, Malaysia Organized by: Faculty of Economics and Muamalat,USIM Page: 321-331